STUDY CONSIDERING THE LEARNING OF BASIC INDIVIDUAL ACTIONS AND COLLECTIVE ACTIONS IN VOLLEY-BALL IN A TEAM OF BEGINNERS - Cristian ȘANTA; Emilia MARIȘ (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2016)
The selection of this study is based on the actual condition nationwide regarding a creation of more efficient learning methodology in volleyball game. Volleyball game known today a new development, due to the vast popularity and spread enjoyed by all ages. Spectacular game, dynamism is given by a variety of processes and technical and tactical actions of attack and defence, acting on the development of human personality, helping to cultivate educational factors aimed at developing collective spirit, imagination and perseverance (Șanta, C: 2016).